Correction to: Tandem affinity purification of AtTERT reveals putative interaction partners of plant telomerase in vivo - Majerská, Jana; Schrumpfová, Petra Procházková; Dokládal, Ladislav; Schořová, Šárka; Stejskal, Karel; Obořil, Michal; Honys, David; Kozáková, Lucie; Polanská, Pavla Sováková; Sýkorová, Eva (Protoplasma, 2018)
In the published online version, the affiliations were mixed up. Corrected affiliation section is shown below. Also, the update has also been reflected in the author group section above.